Pre-scaling up of improved finger millet (Kako-1) variety, at Weyira district, under Halaba zone in Ethiopian - Mekonen Debara; Merkinel Bekele (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
Pre-scaling up of improved finger millet variety (kako-1) was conducted in 2019/20 mehere season in Halaba Zone, two selected kebeles under Weyira District,southern Ethiopia under rain fed conditions through involvement of farmers in participatory demonstration. The demonstration was carried out with the specific objectives:to popularize and demonstrate improved Finger millet technology (Kako-1) and to collect farmers feedback on improved finger millet variety. The demonstration was conducted at layignawu Badana and kufe kebele on farmers field of Weyira Districts on 10ha land coverage totally 20 beneficiary farmers field .Site and beneficiary farmers selection criteria were conducted purposively by cooperating with woreda and kebele extension personnel by willingness to accept technology, land availability and accessibility of the area. Training was given by focusing on agronomic practices and awareness creation for all selected beneficiary farmers and concerned extension personnel. Also, all necessary inputs (10kg/h kako-1 seed,100kg/h NPSB and 150 kg /h Urea) were provided from Hawassa agricultural research center.Yield and farmers feedback data were collected and analyzed by using descriptive statistics applying on SPSS software Accordingly, 2.7 tone/ha average mean grain yield was obtained. According to farmers' feedback, the variety kako-1 has high tilling capacity, high grain yield, early maturity, high biomass yield and quality Therefore the variety need to extended to wide area.So, all concerned bodies need to work to facilitation of further extension of kako-1 variety for Halaba zone and other similar agro-ecological zones to improve finger millet production and productivity of smallholder farmers.